THE EFFECT OF AUDIT QUALITY, FIRM SIZE, AND EARNINGS GROWTH ON EARNINGS QUALITY AT NATIONAL AND LOCAL ENTERPRISES IN THE INDONESIA STOCK EXCHANGE - Hardy Sorialam; Carmel Meiden; Yosef Dema (International Journal of Social Science, 2022)
The goal of this research is to see how audit quality, business size, and earnings growth affect earnings quality. The sample for this study is established through purposive sampling, and it consists of 25 state-owned enterprises listed on the Indonesia Stock Exchange, including financial statement data for the 2016-2020 financial years. Hypotheses are developed using agency theory and signal theory methodologies. The significance of the audit quality variable was 9.6%, the business size variable was 20.8 percent, and the profit growth variable was 0.1 percent, according to the findings of the t-statistical test with a significance level of 5%. According to the findings, audit quality and business size have no impact on earnings quality, while earnings growth has a considerable negative impact.